Formulation development and in vitro and in vivo evaluation of gastroretentive floating drug delivery system of Lafutidine (Asian Journal of Pharmaceutics (AJP), 2014)
Lafutidine a newly developed histamine H2â€receptor antagonist was retained in the stomach and assist in improving the oral sustained delivery of drugs in the gastrointestinal tract. A floating drug delivery system (FDDS) was developedusing the gas forming agents, such as sodium bicarbonate, citric acid with hydrochlorides, such as hydroxyl propyl methyl cellulose (HPMCK 4M, HPMCK15M) and novel Carbopol 71G. Polymer with lower viscosity was found to be beneficialthan higher viscosity polymer in improving the release properties of gastroretentive FDDS. The prepared tablets of various formulations were evaluated for a total floating time, buoyancy lag time, and percentage drug released.The formulation code HF3 having HPMCK4M showed better results it may be useful for prolonged drug release in the stomach to improve thebioavailability and reduced the dose frequency. Nonâ€Fickians release transport was confirmed as the drug release mechanism from the optimized formulation by Korsmeyerâ€Peppas. In vivo study was per formed using the rabbits by Xâ€ray imaging technique; radiological evidences suggest that, a formulated tablet was well floated more than 10 h in rabbitâ€™s stomach.Optimized floating tablets showed no significant changes in the physical appearance, drug content, total buoyancy time, and also in vitro dissolution pattern after storage at 40Â°C/75% relative humidity for 3 months.